Pursuing climate justice through public interest litigation: Theories, practices, and prospects - Hui, Zhang; Karim, Md Rezaull (International Journal of Innovative Research and Scientific Studies, 2025)
Climate change represents a global crisis that transcends borders, affecting every nation and community as climate justice gains prominence and seeking remedies to address climate-related issues becomes crucial. Environmental Public Interest Litigation (EPIL) has emerged as a potent instrument to hold governments and corporations accountable for their contributions to climate change and its consequences. This article explores the theories that underpin climate justice, examines the practical applications of EPIL worldwide, and delves into the intriguing prospect of adopting the Chinese mode of EPIL in transnational climate disputes. As one of the world’s largest economies and greenhouse gas emitters, China plays a pivotal role in the global fight against climate change. This article explores how climate justice can be pursued in China through the avenue of EPIL. It examines the underlying theories that support the concept of climate justice, delves into the practical applications of EPIL in the realm of climate change, analyzes China’s climate legislation and relevant judgments, and discusses the enforcement challenges and prospects for advancing climate justice through EPIL in the Chinese context. The 21st century has witnessed an unparalleled awakening to humanity’s environmental challenges, particularly the global climate change crisis. As the adverse impacts of climate change become increasingly evident, the urgency to address its consequences has led to the concept of climate justice. Climate justice acknowledges the disproportionate burden of climate change on marginalized communities and future generations, emphasizing the need for equitable and sustainable solutions. EPIL has emerged as a legal strategy to uphold climate justice, aiming to bring about systemic change by leveraging the power of the courts to protect the environment and human rights. The urgency of addressing climate change has made it a defining challenge of our era. Its implications extend beyond national borders, affecting ecosystems, economies, and vulnerable populations worldwide. Climate justice underscores the ethical responsibility to address climate change’s disproportionate impacts on marginalized communities and future generations. An important and developing area of environmental law is the use of litigation to seek climate justice. There is an immediate and critical need for strong legal frameworks to tackle the growing threat of climate change and global warming to ecosystems and at-risk populations. A strong theoretical basis for comprehending and progressing climate litigation is provided by concepts like public nuisance, public trust, and human rights. Cases like Milieudefensie et al. [3] in Europe show how lawsuits are being used more and more to enforce climate pledges and rectify environmental damage, while environmental public interest litigation in China has made great strides in holding entities responsible for ecological damage. Establishing more thorough international frameworks and extending these legal procedures outside domestic contexts will be the task going forward. To overcome these restrictions and promote a more united global response to climate change, regional treaties and transnational climate litigation like the ones proposed for ASEAN could be crucial.